2012
DOI: 10.1200/jco.2012.42.4036
|View full text |Cite
|
Sign up to set email alerts
|

Routine Bone Marrow Biopsy Has Little or No Therapeutic Consequence for Positron Emission Tomography/Computed Tomography–Staged Treatment-Naive Patients With Hodgkin Lymphoma

Abstract: A consistent finding of this study was the absence of positive BMBs in PET/CT-assessed stage I to II disease. The omission of staging BMB would not have changed the risk assessment or treatment strategy in this cohort of 454 newly diagnosed patients with HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
155
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(176 citation statements)
references
References 29 publications
16
155
2
3
Order By: Relevance
“…Regarding HL, our results demonstrate a higher sensitivity of PET/ CT over BMB and show that when using the former the number of patients that could be understaged, and therefore treated less than optimal, is marginal. These findings are consistent with previous reports and very recent recommendations [5,6,8,18], and ultimately preclude the routine use of BMB for staging in this group of patients. Whether diffuse uptake should be considered malignant in HL is a controversial area.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding HL, our results demonstrate a higher sensitivity of PET/ CT over BMB and show that when using the former the number of patients that could be understaged, and therefore treated less than optimal, is marginal. These findings are consistent with previous reports and very recent recommendations [5,6,8,18], and ultimately preclude the routine use of BMB for staging in this group of patients. Whether diffuse uptake should be considered malignant in HL is a controversial area.…”
Section: Discussionsupporting
confidence: 92%
“…Whether diffuse uptake should be considered malignant in HL is a controversial area. Most studies found that diffusely increased bone marrow FDG uptake is invariably associated with a negative BMB while positive histologic involvement can be expected in most DLCL cases [8,19]. However, others found that the diffuse pattern in HL could be due to BMI in a small percentage of cases [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal Fluordeoxyglucose (FDG) uptake within the bone or bone marrow, liver, and spleen is highly sensitive for involvement in HL and aggressive NHL and may obviate the need for bone marrow biopsy. 7 In contrast, diffuse increased uptake may occur with abnormal focal uptake, but in HL, diffuse uptake without focal activity often represents reactive hyperplasia and should not be confused with lymphomatous involvement. PET-CT can miss low-volume involvement, typically 20% of the marrow and coexistent low-grade lymphoma in Diffuse Large B Cell Lymphoma (DLBCL), although this rarely affects management.…”
Section: Diagnosismentioning
confidence: 99%
“…It offers better initial staging and risk stratification [3]. FDG-PET often detects occult extranodal disease, notably focal bone marrow lesions [5][6][7]. It rendered useless routine bone marrow biopsy [3].…”
mentioning
confidence: 99%